Urinary Tract Infection in Pregnancy: Bacterial Profile, Antibiogram, Electrolytes and Risk Factors in Otuoke and Environs, Bayelsa State, Nigeria - Buta Tarimotimi Sam; Imarenezor Edobor Peter Kenneth; Efere Y. Samson; Elkanah Edet Usodo; Otumbere Etiefa (Darul Yasin Al Sys, 2026)
Urinary tract infections (UTIs) remain a major health concern during pregnancy due to their potential complications for both mother and fetus, particularly in resource-limited settings. This study investigated the bacterial etiology, antibiotic susceptibility patterns, cytokine responses, electrolyte alterations, and risk factors associated with UTIs among pregnant women in Otuoke and Yenagoa, Bayelsa State, Nigeria. A total of 300 pregnant women attending antenatal clinics in selected hospitals were screened for UTIs, excluding those on antibiotic therapy. Urine, serum, and cerebrospinal fluid samples were processed using standard microbiological and serological techniques, bacterial isolates were identified and subjected to antibiogram testing, and interleukin-10 (IL-10) and electrolyte profiles were measured. Multivariate analysis was used to assess sociodemographic and clinical risk factors. The prevalence of UTI was 18.7% (56/300). Escherichia coli was the predominant pathogen (8.7%), followed by Staphylococcus aureus (2.7%), coagulase-negative staphylococci (2.7%), Proteus spp. (2.0%), Klebsiella pneumoniae (1.4%), Citrobacter spp. (1.0%), and Streptococcus spp. (0.3%). High levels of resistance were observed to ampicillin, gentamicin, and ceftriaxone, whereas ciprofloxacin, norfloxacin, nitrofurantoin, and cotrimoxazole remained effective against most isolates. IL-10 concentrations increased significantly with UTI severity, indicating an enhanced immunological response. Infected participants showed significant alterations in electrolyte and biochemical parameters, including elevated serum urea, creatinine, and proteinuria compared with controls (p < 0.05), with proteinuria demonstrating notable statistical significance (χ² = 13.39, p < 0.05); severe infections were associated with greater disturbances in sodium and potassium balance. Multiparity, low socioeconomic status, and limited educational attainment emerged as significant predictors of UTI occurrence. This study highlights a substantial burden of UTIs among pregnant women in the study area, accompanied by rising antibiotic resistance, and suggests that cytokines—particularly IL-10—and electrolyte abnormalities may serve as useful biomarkers in the immunopathology and diagnosis of UTIs during pregnancy. Routine screening, rational antibiotic use, and targeted health education are essential to reduce the incidence and complications of UTIs in this population.